Semantics and Communication: essays on the Semantics-Pragmatics Divide - Nagase, Daniel Arvage (2022)
The present thesis is an in-depth study of the so-called interpretationist tradition, which is primarily constituted by Quine, Davidson, and Lewis. My objective is to study this tradition from the point of view of the semantics-pragmatics divide, highlighting certain tensions in the work of these authors. The first chapter deals with Quine\'s work, arguing against a certain reading of this work, which sees in Quine a proponent of the thesis of the publicity of meanings. The basic thrust of this chapter is that this reading rests on a misunderstanding of the levels of explanations proposed by him and the location of public meanings relative to these levels. The second chapter analyzes the work of David Lewis, arguing that his explanatory model, which sees sentences as codes for pieces of information about the world and sees the communicative activity as simply an encoding and decoding procedure, is too impoverished to deal with the complexities of language use. Indeed, Lewis himself provides us with the tools to build a more comprehensive model of language use with his notion of linguistic activities as tools for the coordination of rational action. Finally, the last chapter analyzes Davidson\'s work, showing that if, at first, he based linguistic meaning on linguistic conventions, in a second moment, he rejected this explanation in favor of a more complex conception of the communicative situation. My conclusion is twofold. On the one hand, semantics, as the study of the stable characteristics of linguistic utterances, must be reconfigured, being now restricted mostly to grammar. On the other hand, pragmatics, as the study of the interactions between utterances and contexts, must be broadened so as to also include the study of the truth conditions of sentences.